Zika virus, the way forward: Nigeria as case study - Modo, Emmanuel; Okoro, Favour; Orji, Blessing; Njoku, Rex-Clovis (International Journal of Scientific World, 2017)
Zika Virus is a flavivirus that is responsible for an unprecedented current epidemic. It is an emerging mosquito borne virus that is a (+) sense single-stranded RNA virus from the Flaviviridae virus family, Flavivirus genre and the Zika virus specie. Zika virus bears a complex genome and virion structure. Its reproductive cycle in host cell involves virion endocytosis that allows entrance into host cell. Zika virus infection gives symptoms that are usually mild and last for few days and infection can be easily transferred from infected mosquitoes, from a pregnant woman to her fetus, sexual intercourse, blood transfusion, and laboratory exposure. Several methods are made available for the diagnosis of this infection and several ways to prevent this infection such as elimination and control of mosquito, prevention of mosquito bites and public awareness about Zika and mosquitoes. No vaccines are available for treatment yet but common medications are advised for symptoms. The virus has been associated with fetal microcephaly in humans. Information is provided for the epidemiology of Zika virus to evaluate the level of risk for people who may be planning to travel to or are recently returning from areas with possible local transmission. In the African region this is done considering a number of factors and cases in the past. The rapid development of a safe and effective vaccine, genetically modified mosquitoes, use of bacteria, and other innovations are currently worked on to curb the spread of Zika virus.